Students' motivation to attend group guidance based on gender and ethnic - Hariko, Rezki; Nirwana, Herman; Fadli, Rima Pratiwi; Ifdil, Ifdil; Hastiani, Hastiani; Febriani, Rahmi Dwi (Universitas Negeri Padang, 2021)
Although group guidance is believed to be an effective and efficient service to facilitate the development of positive aspects and prevention of negative aspects of students, the frequency of its use for students is not optimal. This study aims to analyze student motivation to follow group guidance and differences in their motivation based on gender and ethnicity. The study used a comparative descriptive method. A total of 690 samples were involved in write-paper-and-pencil questionnaires, namely the students' motivation scale to attend group guidance, which was designed based on the Likert Scale model. We analyzed data using descriptive statistics and different test analysis using independent samples t-test and Bayesian method by applying JASP software. Analysis results showed that most students have the prime motivation to follow group guidance and there are significant differences in student motivation to follow group guidance based on gender, but in terms of ethnicity did not show any significant differences. School counselor can implement the findings of this study in determining group members in group guidance services.